10. EVALUATION OF THE EFFICACY AND SAFETY FOR THE COMBINATION USE OF ORAL AND TOPICAL TRANEXAMIC ACID IN THE TREATMENT OF MELASMA AT HO CHI MINH CITY DERMATOLOGY HOSPITAL (Tạp chí Y học Cộng đồng, 2024)
Objective: To evaluate the effectiveness and safety of oral and topical tranexamic acid in the treatment of melasma.Subjects and methods: A descriptive study of a series of cases with longitudinal follow-up was conducted on 28 female patients with melasma at the Ho Chi Minh City Dermatology Hospital from April 2024 to August 2024.Results: The study subjects had an average age of 47.46 ± 8.23 (34 - 63) years old, 78.57% had a family history of melasma. The assessment of melasma improvement according to the PGA scale showed that 100% of patients had melasma improvement of over 25% (50.00% had good improvement of 51-75%). MASI index had a significant improvement after treatment compared to before treatment with statistical significance with p
Keywords: tranexamic acid; oral and topical; melasma